THE EFFECT OF NOSTRIL BREATHING EXERCISE ON BLOOD PRESSURE REDUCTION IN HYPERTENSIVE PATIENTS WITHIN THE CONTEXT OF FAMILY NURSING: PENGARUH NOSTRIL BREATHING EXERCISE TERHADAP PENURUNAN TEKANAN DARAH PADA KLIEN HIPERTENSI DALAM KONTEKS KEPERAWATAN KELUARGA - Wahyu Widagdo; Oktaviyana Tri Handayani; Ii Solihah (Politeknik Kesehatan Kemenkes RI Jakarta I, 2026)
Hypertension is one of the major public health problems with a high prevalence that can lead to various cardiovascular complications. The management of hypertension is not only carried out through pharmacological therapy but can also be supported by non-pharmacological interventions such as nostril breathing exercise, a breathing technique that alternates between the nostrils and aims to increase parasympathetic nervous system activity, thereby helping to reduce blood pressure. This study aimed to determine the effect of nostril breathing exercise on blood pressure reduction among hypertensive clients within the family context. This study used a case study approach with a nostril breathing exercise intervention conducted for three days on two hypertensive clients with family support. Blood pressure measurements were taken before and after the intervention each day. The results showed a decrease in blood pressure after the intervention, with an average reduction of 10 mmHg in systolic blood pressure and 2 mmHg in diastolic blood pressure. Family involvement in reminding, accompanying, and motivating the clients to perform the exercise also contributed to the success of the intervention. In conclusion, nostril breathing exercise is a simple, safe, and economical non-pharmacological therapy that can help reduce blood pressure in hypertensive clients and can be applied in family nursing practice at home.